A highly stable and hierarchical tetrathiafulvalene-based metal–organic framework with improved performance as a solid catalyst. Issue 9 (6th February 2018) - Souto, Manuel; Santiago-Portillo, Andrea; Palomino, Miguel; Vitórica-Yrezábal, Iñigo J.; Vieira, Bruno J. C.; Waerenborgh, João C.; Valencia, Susana; Navalón, Sergio; Rey, Fernando; García, Hermenegildo; Mínguez Espallargas, Guillermo
Abstract : A highly stable Metal–Organic Framework with a hierarchical structure based on the Fe3 O cluster and a TTF-based ligand is presented. Abstract : Herein we report the synthesis of a tetrathiafulvalene (TTF)-based MOF, namelyMUV-2, which shows a non-interpenetrated hierarchical crystal structure with mesoporous one-dimensional channels of ca. 3 nm and orthogonal microporous channels of ca. 1 nm. This highly stable MOF (aqueous solution with pH values ranging from 2 to 11 and different organic solvents), which possesses the well-known [Fe3 (μ3 -O)(COO)6 ] secondary building unit, has proven to be an efficient catalyst for the aerobic oxidation of dibenzothiophenes.